BARANAK SOUNDS ELECTRONIC AND POST ROCK MUSIC COMPOSITIONS ORIGINATING FROM ORNAMENTATION TECHNIQUES ON TALEMPONG AND SALUANG MINANGKABAU INSTRUMENTS - Gugat, Avant Garde Dewa; Rafiloza, Rafiloza (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Beauty is not always manifested through form, but can be through intent, purpose or expression. Sound of Baranak is a musical composition resulting from the artist's reinterpretation of the ornamentation technique present in Minangkabau traditional music. Musical expression, imagination, musicality, and empiricism are the main keys in the presence of ornamentation. This work is worked on into two repertoires, namely recognize sound and recognize baranak, the two repertoires are worked on with two different musical genres, where the first repertoire the artist chooses the experimental electro genre as a musical expression in order to enrich the processing of compository aspects both from tone variants and rhythm patterns to changes in sound color. Bunyi Baranak is an expression resulting from the reinterpretation of various ornamentation terms in traditional Minangkabau music playing techniques. Ornamentation is a decoration or variation on a work of art with the aim of beautifying it. In traditional Minangkabau musical arts, ornamentation is often present in repetitive repertoire such as talempong pacik, gandang tambua, and saluang dendang. The artist re-dissected the things that underlie the presence of ornamentation in traditional Minangkabau musical arts and then discovered the musical expression, awareness and musicality of traditional arts practitioners. two repertoires, namely Kenali Bunyi and Kenali Baranak, which were worked on the experimental electro and Post Rock music genres.